Knowledge, perceptions and safety practices of COVID-19 infection among healthcare workers in a tertiary health institution, Southwest, Nigeria - Ahmed, Abdul Mumin K.; Ojo, Omobola Y.; Imhonopi, Gloria B.; Oladeji, Funmilayo O.; Oyesola, Olurotimi A.; Alausa, Olanipekun K. (International Journal Of Community Medicine And Public Health, 2020)
Background: Globally, COVID-19 is a topic of concern among the populace and especially with the health care workers. Recent report by NCDC showed that globally as at August 2020, the world had witnessed 17,396,943 cases with 675,060 deaths presenting a case fatality rate of 3.89%. This study assessed the knowledge, perception and safety practices of COVID-19 infection among healthcare workers. Methods: It was a descriptive cross-sectional study. Both qualitative and quantitative methods were used. 410 participants drawn across most units in the hospital. Data analysis was done using SPSS software version 20. Responses were summarized using percentages, and frequencies. Test of association done using chi-square, and level of significance set at 5% (p<0.05). Results: This study found mean population 39.23±9.87 years with modal of 30-39years. All 410 (100.0%) respondents heard about COVID-19 pandemic but further knowledge rating showed 347 (84.6%) had good knowledge. Perception was high at all thematic areas, 275 (67.1%) affirmed that COVID-19 infection was fatal. About 273 (66.6%) strongly agreed that PPE must be worn, similarly, 299 (72.9%) strongly agreed that use of facemask was important for infection prevention strategy. However, observational checklist gave varied opinion on availability and use of PPEs. Conclusions: This study identified a significant gap in information source, knowledge levels especially among lower cadre staff, discrepancies in perceptions of COVID-19 and unavailability of PPEs. There is a need by the government and hospitals management to ensure regular training of all cadres of staff and regular provision of PPEs for the healthcare workers.